Imaging Features of Fibrolamellar Hepatocellular Carcinoma with Contrast-Enhanced Ultrasound - Dong, Yi; Wang, Wen-Ping; Mao, Feng; Zhang, Qi; Yang, Daohui; Tannapfel, Andrea; Meloni, Maria Franca; Neye, Holger; Clevert, Dirk-André; Dietrich, Christoph F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose Fibrolamellar hepatocellular carcinoma (f-HCC) is a rare primary liver tumor. Imaging plays an important role in diagnosis. The aim of this retrospective study was to analyze contrast-enhanced ultrasound (CEUS) features of histologically proven f-HCC in comparison to benign focal nodular hyperplasia (FNH).Materials & Methods 16 patients with histologically proven f-HCC lesions and 30 patients with FNH lesions were retrospectively reviewed regarding CEUS features to determine the malignant or benign nature of the focal liver lesions (FLL). Five radiologists assessed the CEUS enhancement pattern and came to a consensus using the EFSUMB (European Federation of Societies for Ultrasound in Medicine and Biology) guideline criteria.Results Fibrolamellar hepatocellular carcinoma manifested as a single and huge FLL. On CEUS, f-HCC showed heterogeneous hyperenhancement in the arterial phase and hypoenhancement (16/16, 100 %) in the portal venous and late phases (PVLP) as a sign of malignancy. In contrast to the hypoenhancement of f-HCC in the PVLP, all patients with FNH showed hyperenhancement as the most distinctive feature (P < 0.01). 8 f-HCC lesions showed a central scar as an unenhanced area (8/16, 50.0 %), which could also be detected in 53.3 % (16/30) of FNH lesions (P > 0.05).Conclusion By analyzing the hypoenhancement in the PVLP, CEUS imaging reliably diagnosed f-HCC as a malignant FLL. CEUS also showed differentiation between f-HCC and FNH lesions, showing similar non-enhanced central scars, whereas f-HCC lesions showed peripheral hyperenhancement in the arterial phase and early washout in the PVLP.
Keywords: focal nodular hyperplasia (FNH); differential diagnosis; guidelines; contrast-enhanced ultrasound (CEUS); fibrolamellar hepatocellular carcinoma (f-HCC)